Kafka quan wei zhi nan = Kafka : the definitive guide / = Kafka : - Shapira, Gwen; Palino, Todd; Sivaram, Rajini; Petty, Krit (Tu ling cheng xu she ji cong shu, 2022)
Detailed summary in vernacular field.